Downregulation of Wnt3 Suppresses Colorectal Cancer Development Through Inhibiting Cell Proliferation and Migration - Nie, Xiaobo; Xia, Fulin; Liu, Ying; Zhou, Yun; Ye, Wenling; Hean, Panha; Meng, Jiming; Liu, Huiyang; Liu, Lei; Wen, Jianxun; Ren, Xuequn; Chen, Wei-Dong; et al. (Frontiers in Pharmacology, 2019)
The aberrant expression of Wnt3 has linked to several types of human malignancies. However, it is not known for its role in tumorigenesis of colorectal cancer (CRC). Herein, we show that Wnt3 is upregulated in human CRC tissues and cell lines, and is essential for the CRC progression. Knockdown of Wnt3 in human colorectal cancer cells delayed tumor formation in nude mouse xenografts through silencing of canonical Wnt pathway and glycolysis. We further found that silencing of Wnt3 enhanced the sensitivity of CRC cells to cisplatin through inducing apoptotic cell death. Taken together, it demonstrates that Wnt3 is a novel clinical biomarker for the detection of CRC and plays an important role in colorectal tumorigenesis. Therefore, downregulation of Wnt3 will be a valuable strategy in CRC treatment.